INFLUENCE OF CHEMICALS AND PLANT GROWTH REGULATORS ON PLANT GROWTH AND YIELD OF AFRICAN MARIGOLD DURING SUMMER - D. APARNA*, M. L. N. REDDY, A. V. D. DORAJEE RAO, V. V. BHASKAR, P. SUBBARAMAMMA; K. UMA KRISHNA (The Journal of Research ANGRAU, 2021)
The two-year research was conducted during 2017 and 2018 to study the influence of certain chemicals like calcium nitrate, potassium nitrate and plant growth regulators viz., GA3, salicylic acid and homobrassinolide against heat stress tolerance during summer on plant growth and flower yield of African marigold cv. Bidhan Marigold-2. Salicylic acid spray @ 200 ppm once at 30 days after transplanting (DAT) recorded maximum values in terms of flower diameter (4.35 cm), ten flower weight (44.57 g), flower yield (158.39 q ha-1) which was followed by 2% potassium nitrate spray with flower yield of 141.52 q ha-1 whereas untreated plots (control) recorded the lowest values in all the growth and yield paramters